Exploration of Factors Affecting Loan Repayment of Indonesian Village Financial Institutions in Women's Groups Loan - raharjo, taufik; Manurung, Adler Haymans; Sembel, Roy; Yuliati, Retno (Universitas Muhammadiyah Metro, 2024)
This research explores factors that can affect loan repayment of Indonesian Village Financial Institutions in Women Group Lending as a Case Study at Serang Regency. This research uses a qualitative approach by analyzing in-depth interviews with two BUMDesma Directors and Focus Group Discussion with 21 BUMDesma debtors. BUMDesma directors as informants is the BUMDesma director of the BUMDesma of Ciruas and Padarincang sub-districts as chairman and secretary of the BUMDesma association in Serang districts. FGD members are 21 leaders of women group lending as BUMDesma debtors from several sub-districts. Based on the analysis, two important aspects determine the development of BUMDesma Loan Repayment in Serang Regency as a Women's Group Lending Model: the Professionalism of BUMDesma management and the Commitment of BUMDesma debtors.